IOT - Internet das coisas, o que o futuro nos espera - Rodrigues, Laércio (2018)
The growth of intelligent objects with capacity for sensing, processing and communication has increased greatly in recent decades, in this scenario the Internet of Things (IOT), devices, cars, buildings, a house, anything using Arduino sensors and Python programming or any other type of mainstream programming is all this in an internet network and collecting this processed data the internet of things allows collected objects to enter remotely to another and that they be controlled remotely over the internet, thus creating opportunities between the physical world and the virtual world. The IOT enables a large number of new applications, which both academia and industry can take advantage of, such as health, hospitals and today sees videoconference surgeries all thanks to equipment technology. In addition, IOT applications need to address issues of how to collect, store, process, and extract knowledge from data obtained from intelligent objects.